The Production Development of Tofu from Black Bean - ทัศนอุดม อรรณพ; สระพินครบุรี วรรณภา; อนะวัชกุล เมธาวี (KKU Science Journal, 2014)
The objectives of this study: to find the optimum condition of black bean tofu production for replacing soybean tofu consumption that occurred soybean off-flavor and to study the physical, chemical and microbiological characteristics of tofu produced form black bean. Two levels of sodium sulfate (Na2SO4) quantity (0.66 and 1.0%) and coagulation temperature at 90 and 98ºC were studied. Then the % yield of 4 condition treatments were determined. Black bean and soybean tofu attributes were compared by sensory evaluation. The results found that 1% Na2SO4 at 98ºC of coagulation temperature was the most optimum condition for black bean tofu production due to the highest of % yield (80%), without soy bean off-flavor and good texture comparing with soybean tofu. Moreover, black bean tofu contained higher content of anthocyanin (2.08%) than that of soybean tofu. Whereas lipid quantity of the former (1.63%) was less than the later. Sensory evaluation between black bean and soybean tofu showed significant difference (P≤0.05) in all attributes such as color, specific odor, flavor, texture, and overall preference. Furthermore, these moderately like scores of black bean tofu were higher than soybean tofu.